2021
DOI: 10.3390/ani11082266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humic Substances as Feed Additive on the Growth Performance, Antioxidant Status, and Health Condition of African Catfish (Clarias gariepinus, Burchell 1822)

Abstract: In the present study, a possible nature immunostimulant and growth promoter—humic substances (HS) originating from Siberian leonardite mineraloid—were tested on juvenile Clarias gariepinus performance. Feed additive was applied onto commercial pelleted feed at four HS levels—0, 1, 3, and 6% w/w (HS0, HS1, HS3, HS6, respectively). Diets were tested in five repetitions (in total, n = 1800 individuals, mean body weight 28.1 ± 6.2 g) for 56 days. Growth and production parameters, fish condition and somatic indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…This may indicate that humic acid can protect the liver by reducing free radicals produced during liver metabolism (26). Nevertheless, in Prokešová et al (23) study, the activity of ALT, AST, and lactate dehydrogenase enzymes were within the species-specific optimal physiological range, and no differences were observed between the Clarias gariepinus tested groups after 28 and 56 days of HS feeding. Different results may be attributed to animal species, dosage, synthetic form, etc.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This may indicate that humic acid can protect the liver by reducing free radicals produced during liver metabolism (26). Nevertheless, in Prokešová et al (23) study, the activity of ALT, AST, and lactate dehydrogenase enzymes were within the species-specific optimal physiological range, and no differences were observed between the Clarias gariepinus tested groups after 28 and 56 days of HS feeding. Different results may be attributed to animal species, dosage, synthetic form, etc.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, Domínguez-Negrete et al ( 22) found different dietary doses of humic acid did not significantly change the daily gain and feed conversion ratio. In the Prokešová et al (23) study, the humic substances (HS) incorporated into the diet (HS0-6) did not affect the production of Clarias gariepinus. However, broilers fed with FA gained significantly more body weight than those fed with control diets, and their FCR was also lower than those fed with control diets (11).…”
Section: Discussionmentioning
confidence: 94%
“…Some researchers believe that the content of CHOL, TP and Glu is positively correlated with the metabolic function of fish and their ability to adapt to harsh ecological environments. However, other studies have proposed that people with low plasma protein and albumin content have strong adaptability to the environment and a strong constitution 100 . The levels of ALB and TP in serum of crucian carp with haemolytic ascites disease are significantly lower than those of healthy fish.…”
Section: Blood Biochemical Indicesmentioning
confidence: 88%
“…However, other studies have proposed that people with low plasma protein and albumin content have strong adaptability to the environment and a strong constitution. 100 The levels of ALB and TP in serum of crucian carp with haemolytic ascites disease are significantly lower than those of healthy fish. In these cases, ALB reaches levels that are below 1% of that of healthy fish, while creatinine is significantly higher than that of healthy fish.…”
Section: Organic Compounds In the Bloodmentioning
confidence: 96%
“…Prokešová et al [ 1 ] tested the effects of four levels (0, 1, 3, and 6% w / w ) of humic substances (HS) as natural immunostimulants and growth promoters in juvenile African catfish ( Clarias gariepinus ) during a 56-day exposure. Although growth was not improved by HS addition, moderately positive effects were observed regarding health status and antioxidant parameters, especially in the group receiving 3% HS.…”
mentioning
confidence: 99%